Functions of volume‐sensitive and calcium‐activated chloride channels. Issue 4 (28th April 2014) - Hoffmann, Else Kay; Holm, Niels Bjerre; Lambert, Ian Henry
Abstract The review describes molecular and functional properties of the volume regulated anion channel and Ca2+‐dependent Cl− channels belonging to the anoctamin family with emphasis on physiological importance of these channels in regulation of cell volume, cell migration, cell proliferation, and programmed cell death. Finally, we discuss the role of Cl− channels in various diseases. © 2014 IUBMB Life, 66(4):257–267, 2014